Multigenerational effects of maternal undernutrition - Einstein, Francine H. (2014)
Intrauterine exposure to reduced nutrient availability can have major effects in determining susceptibility to chronic disease later in life. Martínez et al. (2014) demonstrate multigenerational effects of poor maternal nutrition and evidence of germ-line transmission through alterations in DNA methylation.